2019
DOI: 10.1099/acmi.imav2019.po0008
|View full text |Cite
|
Sign up to set email alerts
|

Host genome depletion to determine the evolution, genetic diversity and transmission patterns of full genome sequences of African swine fever genotype IX from Uganda

Abstract: African swine fever (ASF) is a highly contagious viral haemorrhagic disease of domestic pigs, wild boar and feral swine. It is caused by the only DNA arbovirus, African swine fever virus (ASFV), which is the only member of the family Asfarviridae and is transmitted by the soft ticks in the genus Ornithodoros. ASF results in mortalities of up to 100% and exhibits different epidemiological patterns in Africa, Europe and Asia. This ASFV has recently spread to other countries in Europe and is also now present in A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The ASFV p72 genotype IX was recovered from domestic pigs and warthogs. This genotype is described as the most predominant in Uganda and Kenya [ 42 ], but also, it was described in DRC [ 50 , 53 ] and Tanzania [ 56 , 62 ]. Although associated with lethal ASF outbreaks [ 21 , 47 , 48 ], an increasing number of studies reported the genotype IX in asymptomatic domestic pigs in Tanzania [ 56 ], DRC [ 50 ], Uganda [ 44 ], and Kenya [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ASFV p72 genotype IX was recovered from domestic pigs and warthogs. This genotype is described as the most predominant in Uganda and Kenya [ 42 ], but also, it was described in DRC [ 50 , 53 ] and Tanzania [ 56 , 62 ]. Although associated with lethal ASF outbreaks [ 21 , 47 , 48 ], an increasing number of studies reported the genotype IX in asymptomatic domestic pigs in Tanzania [ 56 ], DRC [ 50 ], Uganda [ 44 ], and Kenya [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Zambia recorded a wider variety of ASFV p72 genotypes with seven genotypes being reported to circulate in the country, namely genotypes I, II, VIII, XI, XII, XIII, and XIV. [40] p72, p54, p30, CVR II Domestic pig [41] p72, p54 I Domestic pig [22] p72 I, II, VIII, XI, XII, XIII, XIV Domestic pig and tick [23] p72, CVR I, VIII Tick and domestic pig [17] p72, p54, CVR I, II, XIV Domestic pig [42] WGS IX Domestic pig Uganda (10) [43] p72, p54, CVR IX Domestic pig [44] p72, p54, CVR IX Domestic pig [45] p72, p54, CVR IX Domestic pig [46] WGS IX Domestic pig [47] p72, p54, CVR IX Domestic pig [21] p72, p54, CVR IX, X Domestic pig [22] p72 IX Domestic pig [23] p72, CVR IX, X Domestic pig [48] p72, p54, CVR, TK IX Domestic pig [49] p72, CVR II, V, VI, VIII Domestic pig…”
Section: Asfv Genotypesmentioning
confidence: 99%